2007
DOI: 10.1089/jmf.2006.147
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Hypolipidemic Effects of Black Soybean Anthocyanins

Abstract: The effect of anthocyanins extracted from black soybean (Glycine max L.) seed coats on body weight, adipose tissue weight, and serum lipids was evaluated in rats fed a high fat diet (HFD). Rats were raised on a normal diet (ND) (based on the AIN-93M diet), HFD (ND supplemented with 16% lard oil), HFD containing 10% black soybean, and HFD containing 0.037% black soybean anthocyanins (equivalent to that in the 10% black soybean diet). Weight gain was significantly lowered in the rats fed HFD plus black soybean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 16 publications
9
76
0
4
Order By: Relevance
“…Bhatt is traditionally prepared in an iron kadhai to make chudkani, bhatwani and thatwani. The anthocyanins in black soybean seed coat have anti-obesity effect (Kwon et al, 2007). Earlier reports have indicated that by various treatments nutritional quality of legume can be changed to increase its nutrient utilization efficiency (Jood et al,1986, Mubarak,2005Sharma et al, 2011;Odiba, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bhatt is traditionally prepared in an iron kadhai to make chudkani, bhatwani and thatwani. The anthocyanins in black soybean seed coat have anti-obesity effect (Kwon et al, 2007). Earlier reports have indicated that by various treatments nutritional quality of legume can be changed to increase its nutrient utilization efficiency (Jood et al,1986, Mubarak,2005Sharma et al, 2011;Odiba, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Kwon et al evaluated the effect of black soy anthocyanins addition on an hyperlipidic diet of rats and observed 23 and 20% reduction in triglycerides and cholesterol levels, respectively, and an increase of 37% in the HDL-cholesterol fraction (Kwon, et al, 2007). In contrast to the present, a recent study showed that FJP could enhance HDL-cholesterol in obese rats (Lenquiste et al, 2012).…”
Section: Nsmentioning
confidence: 70%
“…The impact of anthocyanins on the serum lipids of rats fed high-fat diets is controversial 7,10,21 . Kwon et al 7 found that SD rats fed 10% black soybean or 0.037% anthocyanin extract presented lower total serum cholesterol and triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al 7 found that SD rats fed 10% black soybean or 0.037% anthocyanin extract presented lower total serum cholesterol and triglyceride levels. However, studies with obese mice treated with a high-anthocyanin beverage or diet corroborate our findings 10,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation